Outcomes of Vascular Intervention in Diabetic Patients with Peripheral Arterial Disease - Mahfujul Z. Haque; Rumyah Rafique; Syeda Reesha; Shahrin Khan; Arif Hussain; Mashkur Husain (University Library System, University of Pittsburgh, 2022)
BACKGROUND:   Peripheral arterial disease (PAD) is more prevalent and often presents as more severe in patients with diabetes mellitus (DM) compared with those without DM. Although some patients may be asymptomatic, symptoms ranging from exertional leg heaviness and fatigue to acute limb loss are possible. PAD has significant physical and psychiatric health consequences, thus management with medical therapy and lifestyle changes are indicated. However, peripheral vascular intervention (PVI) is an increasingly popular method used in patients failing conservative management. The association of PVI with health status in diabetic patients has yet to be determined.   METHODS: We analyzed the clinical response to PVI in DM (n=203, 52%) compared with non-DM patients (n=183, 48%), using the Peripheral Arterial Questionnaire (PAQ) for patients during baseline and a maximum 6 months after PVI. 502 patients participated with an exclusion of 116 patients from our analysis due to progression of acute limb ischemia and incomplete data collection. Our finalized study population comprised 386 consecutive patients with symptomatic PAD who had also received PVI treatment during the aforementioned time frame. Our patient population received PVI treatment in the year 2012 at the St. John Hospital and Medical Center in Detroit, MI. We used the PAQ summary score, which summarizes the patients' level of physical and social function, patient symptoms, and overall quality of life before and after the procedure. This represented the PAD-related Quality of Health (QOH). Our score range is between 0 (lowest health quality) and 100 (highest health quality).     RESULTS: Compared with non-DM patients, those with DM were more likely to have a history of prior PVI, an increased prevalence of PAD risk factors, and significantly lower QOH scores at baseline (32.7 +/- 20 vs 37.5 +/- 20.6, p=0.02). After adjustment for baseline confounding, neither the baseline, the change, nor the final summary scores were significantly different between groups. This suggests similar symptomatic and functional improvement in non-DM and DM patients post-PVI.    CONCLUSIONS: Following PVI, PAD-specific health status showed a similar improvement in patients with and without DM, illustrating that use of this strategy among patients with multiple comorbidities or diffuse PAD as useful.    Key Words: peripheral arterial disease, peripheral vascular intervention, diabetes mellitus, quality of life    Figure or Table:  Table 5. Comparison of the Summary Score of 6 PAQ Domains Using Median Scores from Mann Whitney U Test of DM and Non-DM Patients in Detroit, MI, USA   PAQ domain DM Non-DM P-Value Physical limitation 16.6 (75.4) 25.0 (79.8) 0.06 Symptoms 23.6 (75.4) 27.7 (79.8) 0.24 Symptom stability 25.0 (75.4) 25.0 (79.8) 0.28 Social limitation 16.6 (75.4) 25.0 (79.8) 0.07 Treatment satisfaction 0.0 (75.4) 0.0 (79.8) 0.42 Quality of life 16.6 (75.4) 25.0 (79.8) 0.06 Summary score 18.7 (75.4) 26.0 (79.8) 0.049